2011
DOI: 10.1111/j.1574-6941.2011.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacterial community dominated by a distinct clade in acidic soil of a waterlogged deciduous forest

Abstract: Members of the Actinobacteria are among the most important litter decomposers in soil. The site of a waterlogged deciduous forest with acidic soil was explored for actinobacteria because seasonality of litter inputs, temperature, and precipitation provided contrasting environmental conditions, particularly variation of organic matter quantity and quality. We hypothesized that these factors, which are known to influence decomposition, were also likely to affect actinobacterial community composition. The relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…However, higher number of detected compounds was found in acidic soils and even though this result is based only on a small dataset, we think that acidic soils may harbor novel actinobacterial diversity. That result is supported by our previous description of high erm gene variability and of a new suborder of actinobacteria dominating actinobacterial communities at both of the studied acidic sites (Trebon - [20,50]; Zakopana - [17]).…”
Section: Discussionsupporting
confidence: 88%
“…However, higher number of detected compounds was found in acidic soils and even though this result is based only on a small dataset, we think that acidic soils may harbor novel actinobacterial diversity. That result is supported by our previous description of high erm gene variability and of a new suborder of actinobacteria dominating actinobacterial communities at both of the studied acidic sites (Trebon - [20,50]; Zakopana - [17]).…”
Section: Discussionsupporting
confidence: 88%
“…The Proteobacteria phylum includes many of the bacteria responsible for nitrogen fixation (Chen et al 2003; Wang et al 2015) and a wide variety of pathogens (Tsolis 2002). Actinobacteria play an important role in the decomposition and humus formation processes (Kopecky et al 2011). The ecology and metabolism of Acidobacteria is not well understood because the majority of these bacteria have not been cultured (Sun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At the Z site, the most diverse bacterial communities (based on the number of T-RFs) and nonproducer type erm genes suggested that the diversification of bacteria was conditioned by large amounts of recalcitrant litter (16). The Z site conditions selected for a small but very specific actinobacterial community (lowest richness and lowest percentage of actinobacteria in the community by quantity), which consisted of Acidimicrobidae and sequences related to the recently described Trebon clade occurring in low-pH soil (33). At the M and D sites, the recalcitrant litter led to relatively high C content and corresponded with high abundance of both bacteria and actinobacteria (41) and also with the highest proportion of actinobacteria in the bacterial community.…”
Section: Discussionmentioning
confidence: 99%